Cosmetic and oncological outcome of different oncoplastic techniques in female patients with early central breast cancer. (May 2021) - Essa, Mohamed S.; Ahmad, Khaled S.; Salama, Ahmed M.F.; Zayed, Mohamed E.
Abstract: Background: Breast conservative surgery (BCS) was absolutely contraindicated in centrally located breast cancer (CLBC). This study evaluates the short-term oncological and cosmetic outcomes of different oncoplastic procedures after resection of CLBC. Material and methods: This prospective study includes 40 female patients with CLBC who underwent different oncoplastic techniques and had the Grisotti, Melon slice, Round block, and Batwing mastopexy techniques. Cosmetic outcomes were evaluated by patients and surgeons, in addition to assessing the oncological outcome. Results: The patients evaluated the postoperative cosmetic result. They were described as excellent in 27 patients (67.5%), good in 11 patients (27.5%), fair in 2 patients (5%) with neither poor nor bad results, with a mean of 4.44 ± 0.6 ( P  = 0.002). In comparison, the surgeons evaluation was 10 points in 8 patients (20%), 9 points in 7 patients (17.5%), 8 points in 12 patients (30%), 7 points in 3 patients (7.5%), 6 points in 7 patients (17.5%), and 5 points in 3 patients (7.5%), with a mean of 7.54 ± 1.52, ( P  = 0.001). Conclusions: The Grisotti technique is associated with a better cosmetic result when reconstructing the central defect in moderate-sized breasts. Batwing mastopexy and round block techniques can be used to resect the central tumors with an excellent cosmetic outcome. Highlights: OPS techniques have reasonable cosmetic and oncological outcomes in central quadrant reconstruction. Grisotti technique has better cosmetic result than Melon slice technique. Both Batwing mastopexy and round block techniques have an excellent cosmetic outcome.